2014
DOI: 10.1186/s12966-014-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Family Home: a qualitative exploration of physical environmental influences on children’s sedentary behaviour and physical activity within the home space

Abstract: BackgroundRecent changes in home physical environments, such as decreasing outdoor space and increasing electronic media, may negatively affect health by facilitating sedentariness and reducing physical activity. As children spend much of their time at home they are particularly vulnerable. This study qualitatively explored family perceptions of physical environmental influences on sedentary behaviour and physical activity within the home space.MethodsHome based interviews were conducted with 28 families with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 53 publications
3
65
0
5
Order By: Relevance
“…These complex interrelations between electronic media and sedentary behaviour in children suggest that interventions that focus solely upon the provision or removal of electronic devices from the home may be overly simplistic and unlikely to produce consistent changes in behaviour. Indeed, qualitative studies have shown that diverse features of the home social and physical environment interact to influence children’s physical activity and sedentary behaviour [40,41]. Researchers and practitioners will need to acknowledge these issues during intervention design.…”
Section: Discussionmentioning
confidence: 99%
“…These complex interrelations between electronic media and sedentary behaviour in children suggest that interventions that focus solely upon the provision or removal of electronic devices from the home may be overly simplistic and unlikely to produce consistent changes in behaviour. Indeed, qualitative studies have shown that diverse features of the home social and physical environment interact to influence children’s physical activity and sedentary behaviour [40,41]. Researchers and practitioners will need to acknowledge these issues during intervention design.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, this indicator is very difficult to examine based on a lack of empirical data adhering to the grading framework. 5 Indeed, familial determinants and correlates of sport and physical activity were not systematically studied in national representative surveys.…”
Section: Family and Peers: Cmentioning
confidence: 99%
“…For instance, it is known that a child's level of social activity is strongly influenced by such factors as parental expectations and support, the modelling of siblings, and the opportunities that exist within their community to participate in social activities [43][44][45]. In this study resources did not permit these specific issues to be explored in any detail, but there were only a small number of children with out-of-school activities, and most of these were in the control group.…”
Section: Discussionmentioning
confidence: 99%